Spatial Distribution of a Porphyrin-Based Photosensitizer Reveals Mechanism of Photodynamic Inactivation of Candida albicans - Voit, Thomas; Cieplik, Fabian; Regensburger, Johannes; Hiller, Karl-Anton; Gollmer, Anita; Buchalla, Wolfgang; Maisch, Tim (Frontiers in Medicine, 2021)
The antimicrobial photodynamic therapy (aPDT) is a promising approach for the control of microbial and especially fungal infections such as mucosal mycosis. TMPyP [5,10,15, 20-tetrakis(1-methylpyridinium-4-yl)-porphyrin tetra p-toluenesulfonate] is an effective photosensitizer (PS) that is commonly used in aPDT. The aim of this study was to examine the localization of TMPyP in Candida albicans before and after irradiation with visible light to get information about the cellular mechanism of antifungal action of the photodynamic process using this PS. Immediately after incubation of C. albicans with TMPyP, fluorescence microscopy revealed an accumulation of the PS in the cell envelope. After irradiation with blue light the complete cell showed red fluorescence, which indicates, that aPDT is leading to a damage in the cell wall with following influx of PS into the cytosol. Incubation of C. albicans with Wheat Germ Agglutinin (WGA) could confirm the cell wall as primary binding site of TMPyP. The finding that the porphyrin accumulates in the fungal cell wall and does not enter the interior of the cell before irradiation makes it unlikely that resistances can emerge upon aPDT. The results of this study may help in further development and modification of PS in order to increase efficacy against fungal infections such as those caused by C. albicans.